Kajian pemanfaatan pakan maggot (Hermetia illucens) sebagai pakan alternatif terhadap pertumbuhan benih ikan gabus (Channa striata) - Zuhdi, Imam; Prasetiyo, Himawan; Sasongko, Agung Setyo (Departemen Akuakultur FPIK UNDIP, 2024)
Research on the utilization of maggot feed (Hermetia illucens) as an alternative feed for the growth of snakehead fish (Channa striata) fry is rarely conducted until now. Therefore, observation of using maggot feed in this research is necessary to obtain the appropriate usage techniques. This study aims to determine the effect of adding maggot feed (H. illucens) on the growth of snakehead fish fry (C. striata). The research follows a completely randomized design (CRD) with 4 treatments and 1 replication. The treatments in this study consist of Treatment 1 as the control with 100% commercial feed, Treatment 2 with 25% maggot meal and 75% commercial feed, Treatment 3 with 50% maggot meal and 50% commercial feed, and Treatment 4 with 75% maggot meal and 25% commercial feed. The size of the snakehead fish fry is 5-7 cm, and they are placed in Container Boxes with a stocking density of 10 fish per treatment. Test feeds for Treatments B, C, and D are prepared by mixing commercial feed and 1% egg white as a binder, while the control feed is prepared using 100% maggot feed with egg white. The test fish are reared for 28 days and fed the test feed three times a day. The research parameters consist of specific growth rate (SGR), absolute weight growth, absolute length growth, and fish feed conversion ratio (FCR). The provision of maggot feed with good content results in optimum growth of snakehead fish fry. The optimum results are obtained in Treatment C.